Plasma Concentrations of Urea and Creatinine in Primary School Children in Ujung Pandang - Gatti H. Hamma; Syarifuddin Rauf; Dasril Daud; Agnes Kwenang (Paediatrica Indonesiana, 1991)
A study of plasma concentrations of urea creatinine in 202 primary school children aged between 6 to IS years was carried out in Ujung Pandang from November 1988 through February 28, 1989. Sampling was done using multi-stage random sampling method. Plasma urea concentrations were not affected by sex, age and nutritional status. Normal distribution of plasma urea concentrations in P2.J and P97.J were 8.13 mg/dl and 24.09 mg/dl respectively (95% confidence level). There was no difference of creatinine concentration between the two sexes. The overall mean creatinine concentrations was significantly higher in the wellnourished group (0.73 Â± 0.081) mg/dl) as compared to PEM group (0.63 Â± 0.066 mg/dl). This study revealed a correlation between age and plasma creatinine concentrations in the well nourished (r=0.46. p<0.01) as well as in PEM (r=0.37, p<0.01) group. Hence, normal distribution of plasma creatinine concentrations should be base on values in each age group. This study showed no correlation between plasma urea and creatinine concentrations.